CALCIUM CARBONATE DISSOLUTION IN DEEP SEA SEDIMENTS: RECONCILING MICROELECTRODE, PORE WATER AND BENTHIC FLUX CHAMBER RESULTS - Jahnke R.A.; Jahnke D.B. (My University, 2004)
We report the benthic fluxes of O2, titration alkalinity (TA), Ca2+, NO3-, PO43-, and Si(OH)4 from in situ benthic flux chamber incubations on the Ceara Rise and Cape Verde Plateau and compare them to previously published results. We find within analytical uncertainty that the TA flux is twice the calcium flux, suggesting that dissolution/precipitation of CaCO3 is the principal mechanism controlling benthic TA and Ca2+ fluxes. At sites where the sediments contain significant (>35%) CaCO3 and the overlying waters are supersaturated with respect to CaCO3, the ratios of the total dissolution rate to the remineralization rate are significantly less than at all other study sites. We propose that these observations can be explained by precipitation of fresh CaCO3 at the supersaturated sediment surface followed by redissolution deeper in the sediments because of metabolically-produced CO2. A numerical simulation is presented to demonstrate the feasibility of this explanation. In addition, surface exchange reactions in high-CaCO3 sediments coupled with high rates of particle mixing may also impact rates of metabolic dissolution and depress chamber-derived estimates of carbonate alkalinity and calcium benthic fluxes. These results suggest that at supersaturated, high CaCO3 locations, previous models of sediment diagenesis may have overestimated the impact of metabolic dissolution on the preservation of CaCO3 deposited on the sea floor.